(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
This study aimed at indicators of technical analysis and their impact on a group of trading stock indices related to it, by standing on the methods used in technical analysis and its various models, diagnosing the obstacles and difficulties that the participants face in predicting stock prices, and proposing solutions and recommendations to overcome and overcome them. From a scientific and practical perspective. Where the research community consisted of (25) Iraqi private commercial banks, while the research sample consisted of (3) banks with a percentage of (12%) of the research community. The study used the analytical approach to the financial statements during the period between (1/2/ 2022-30/4/2022), where the financial data (closing prices) for the shares of the banks of the research sample were calculated through the mathematical equations of the technical indicators, and then they were represented in the form of graphs to clearly identify the trading signals (buying and selling), and then the data was analyzed Using the statistical program (SPSS) to test the research hypotheses, where the results showed an effect between technical indicators (Relative Strength Index, Stochastic Indicator), and predicting stock price movement (sell signal, buy signal). The study came out with a number of recommendations, the most important of which is the need for private Iraqi commercial banks to enhance the position of technical analysis as a qualitative tool used to improve the investor’s decision and increase the ability to analyze and forecast. The Academy should increase the spotlight on technical analysis by encouraging research and studies because of its great importance to the decision to invest in stocks in the future.